Basic Marketing / A Global-Managerial Approach - Mccarthy Jerome E; Perreault William D (Irwin Mcgraw-Hill, 1999)
Marketing's Role in the Global Economy, Marketing's Role within the Firm or Nonprofit Organization, Focusing Marketing Strategy with Segmentation and Positioning, Evaluating Opportunities in the Changing Marketing Environment, Demographic Dimensions of Global Consumer Markets, Behavioral Dimensions of the Consumer Market, Business and Organizational Customers and Their Buying Behavior, Improving Decisions with Marketing Information, Elements of Product Planning for Goods and Services, Product Management and New-Product Development, Place and Development of Channel Systems, Distribution Customer Service and Logistics, Retailers and Wholesalers and Their Strategy Planning, Promotion and Introduction to Integrated Marketing Communications, Personal Selling, Advertising and Sales Promotion, Pricing Objectives and Policies, Price Setting in the Business World, Developing Innovative Marketing Plans, Appendices, Author and Subject Index. Includes CD-Rom.